Implementasi Gerakan Literasi Melalui Pembiasaan Membaca Pada Siswa SD SEGUGUS II AIMAS - Nova Nugrahaeni; Heru Subrata (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The aims of this study was to conduct a literacy campaign in a second group of Idolmaster primary schools and to identify factors that hinder and support literacy campaigns. A descriptive qualitative survey was used as the survey form. The subjects of this study were students, principals, and reachers. The data collection methods used by the researchers were observations, interviews, and recordings. Data analysis techniques use Miles and Huberman's qualitative models to reduce, present and draw conclusions from data. It was found that the implementation of the Seggas II Idolmaster Primary School Literacy Campaign is still in the stage of specialization or familiarization. Interviews and observations by researchers confirm this.